Leveraging and corporate performance : evidence from Sarawak based public listed companies - Chua, Chee Bing (Universiti Malaysia Sarawak (UNIMAS), 2014)
Capital structure decision is vital that it would affect the corporate performance in terms of profitability and investment value. Leveraging, one of capital structure decision involves extending the company resources through external resources such as loans and borrowing, either for long term or short term. Many financial advocates proposed that leveraging improves corporate performance by exploring the greater market opportunities, achieving economies of scale and producing better financial ratios in terms of valuation. However, theories may not always work in real life environment. This study takes on twenty five selected public listed companies in Bursa Malaysia which criteria to be Sarawak-based companies. Sarawak is indeed the best choice for study due to wide geographical and coverage areas, which basically push these companies to incur more costs to reach every corner of the market to excel in a competitive market condition. The relationship between leveraging and corporate performance is undertaken by using financial ratios as indicator, where correlation analysis is used to determine the relationship between independent variable (represented by Gearing Ratio) with dependent variables ( represented by ROA, ROE, PM and EPS ratio). The findings revealed that Gearing Ratio has significant positive negative with ROA, with the remaining relationship were insignificant. Further VI revelation indicated that Short Term Borrowing factored the positive relationship with both ROA and ROE. This suggests that these companies preferred external borrowing while preferring to commit in higher short term borrowing rates rather than tied up to long commitment. In reflect of negative impact of leveraging, we encourage companies to acquire funds internally or taking up long term borrowing to increase fund.